2013
DOI: 10.1111/aogs.12218
|View full text |Cite
|
Sign up to set email alerts
|

Simulator training and non‐technical factors improve laparoscopic performance among OBGYN trainees

Abstract: Simulator training and non-technical factors appear to improve the laparoscopic performance among trainees/residents in obstetrics and gynecology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 32 publications
1
43
0
Order By: Relevance
“…The Begg test and Egger test were both significant (p = 0.014 and p = 0.006, respectively), indicating the possibility of publication bias. The most evident outliers were the studies by Nugent (left upper quadrant) and Ahlborg et al . (right lower quadrant).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Begg test and Egger test were both significant (p = 0.014 and p = 0.006, respectively), indicating the possibility of publication bias. The most evident outliers were the studies by Nugent (left upper quadrant) and Ahlborg et al . (right lower quadrant).…”
Section: Resultsmentioning
confidence: 99%
“…An overview of the aptitude tests used to measure visual–spatial ability is shown in Appendix S4. In five groups of participants, laparoscopic skills were measured in the OR . The mean correlation in DS 0 (dataset in which unreported non‐significant correlations are coded as 0) was 0.32 (95% CI 0.25–0.39; p < 0.001), Q was statistically significant (74.55; p < 0.001) and I 2 was 53%, indicating above‐moderate heterogeneity (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, residents show increased self-efficacy after simulation in disclosing a medical error to a standardized patient (19), and multidisciplinary teams show improved self-efficacy after crew resource management-based operating room team training with simulation (12). In randomized controlled trials comparing simulation-based training with traditional educational techniques, residents in obstetrics and gynecology show favorable increases in self-efficacy after simulation in laparoscopic procedural techniques compared with nonsimulation trained peers (2), and simulator-trained nurses show greater self-efficacy in communication skills compared with case-based trained nurses (9).…”
Section: Diffusion and Disseminationmentioning
confidence: 99%
“…This is very unfortunate, as especially this aspect of emerging self-efficacy can potentially be harmful if the resident has developed an unjustified perception of performance 22. These findings are in contrast to the study of Ahlborg et al, 6 who found evidence for a correlation between higher self-efficacy and shorter laparoscopic operation duration in gynaecology residents.…”
Section: Discussionmentioning
confidence: 83%